Nanomaterials in Daily Life : Compounds, Synthesis, Processing and Commercialization - Abdullaeva, Zhypargul (Springer International Publishing : Imprint: Springer, 2017)
This book describes nanomaterials used and existing in the environment, food industry and packaging, health care products and cosmetics, housekeeping, nanomaterials for cleaning purposes, architectural building products, medicine, clothing and textile, smart electronics and sensors. Each chapter provides basic knowledge on synthesis of nanomaterials by biological approaches. Fundamental terms are defined, followed by explanatons, examples, visual photographs, schemes and illustrations. .
Keywords: Materials science.; Pharmacology.; Food -- Biotechnology.; Nanoscale science.; Nanoscience.; Nanostructures.; Electrical engineering.; Environmental chemistry.; Nanotechnology.; elektronické knihy; electronic books